The hydropolitics of dams engineering or ecosystems? - Everard, Mark (London Zed Books, 2013)
The Hydropolitics of Dams charts the troubled waters of 'heavy engineering' approaches to ecosystem management, exploring the history, benefits and problems of large dams. It then explores diverse ecosystem-based approaches to, and the political, economic and legal dimensions of, management of human interactions with the water cycle, concluding that a synthesis of approaches is needed.
Development, water, and dams -- Water in the postmodern world -- Rethinking water and people -- Annexe: Principles for sustainable water sharing.
Includes bibliographical references (pages 273-294) and index.
Keywords: Dams -- Environmental aspects; Ecosystem management; Water-supply engineering; Sustainable development